Analisa Algoritma Noekeon Untuk Mengamankan File Video - Milawati Milawati; Natalia Silalahi; Kennedi Tampubolon (STMIK Budi Darma, 2021)
Along with the times, human needs are increasing, including the need for information. Therefore, sending and storing files via electronic media requires a process that is able to guarantee the safety and integrity of the file. To ensure the safety and integrity of a file, it requires a file. The encryption process is carried out when the file is sent. This process will change the original file into a secret file that cannot be read. Meanwhile, the decryption process is carried out by the recipient of the sent file. The secret file received will be changed back to the original file. By means of this encryption, the original file will not be read by unauthorized parties, but only by the recipient who has decryption key. Currently, one of the methods used to secure files is to use a cryptographic system by encoding the contents of the information (plaintext) into incomprehensible content through an encryption process (enchiper), and to retrieve the original information, a encryption process is carried out ( dechiper). accompanied by using the correct key. However, in line with the development of encryption or cryptography, efforts to obtain this key can be done by anyone, including those who are not authorized to choose the information. Therefore, research on cryptography will always evolved to obtain ever stronger cryptographic algorithms, making attempts to illegally decode cryptography illegally become more difficult